Ta’liim Maharat Qira'at Al-Lughah Al-‘Arabiah An-Naatiqiina Bigairiha (Diraasat Wasfiat ‘Ani Ta’lim Al-Qira'at Al-‘Arabiah Bima’had Al-Imaan Al-Islamii Lil Banati): تعليم مهار ة قر اءة اللغة العر بية الناطقين بغير ها (در اسة وصفية عن تعليم القر اءة العر بية بمعهد الإيمان الإسلامي للبنات) - farkhan rahayu; Andri Warseto; Suparmanto Suparmanto; Hani Nurlaeli Wijayanti (Cordova Journal, 2024)
Islamic Boarding School Al-Iman for girls seeks to realize the reading skills of students through teaching Muthola'ah using the book “Al-Qiro'ah Arrosyidah” starting from second grade to sixth grade. For this reason, Islamic Boarding School Al-Iman for girls establishes standard methods and steps for teaching Muthola'ah for all grade levels, so that teachers can adapt the teaching and learning process to the goals set by the boarding school. This prompted researchers to further research the teaching Muthola'ah in second grade. This study aims to explain the teaching of reading skills for the second grade at the Islamic Boarding School Al-Iman for girls. The method used is a descriptive method by thoroughly explaining the teaching of reading skills at the Islamic Boarding School Al-Iman for girls.